2017
DOI: 10.1111/sjop.12385
|View full text |Cite
|
Sign up to set email alerts
|

Does a short self‐compassion intervention for students increase healthy self‐regulation? A randomized control trial

Abstract: The primary aim of this study was to examine the effects of a two-week self-compassion course on healthy self-regulation (personal growth self-efficacy and healthy impulse control) and unhealthy self-regulation (self-judgment and habitual negative self-directed thinking) in university students. We also examined the effects on self-compassion, anxiety and depression. Students (N = 158, 85% women, mean age = 25 years) were randomized to an intervention group and a waiting-list control group in a multi-baseline r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 27 publications
(46 reference statements)
8
33
1
3
Order By: Relevance
“…Indeed, the short-lived nature of the effects is in line with other collective gathering studies that have also suggested brief temporal effects (Páez et al 2015;Rimé et al 2011). These findings happen to be comparable to other brief relaxation and mindfulness interventions that have been shown to improve selfreported anxiety and fatigue (Chad-Friedman et al 2017;Dundas et al 2017). Finally, the lack of randomization and absence of an active control group means that non-specific unknown mechanistic factors may have influenced the findings (e.g., even though no significant differences were found between the experimental and control groups at pre-test in any of the study variables, the groups could have differed on variables that we chose not to assess as part of this pilot design).…”
Section: Limitations and Future Researchsupporting
confidence: 76%
“…Indeed, the short-lived nature of the effects is in line with other collective gathering studies that have also suggested brief temporal effects (Páez et al 2015;Rimé et al 2011). These findings happen to be comparable to other brief relaxation and mindfulness interventions that have been shown to improve selfreported anxiety and fatigue (Chad-Friedman et al 2017;Dundas et al 2017). Finally, the lack of randomization and absence of an active control group means that non-specific unknown mechanistic factors may have influenced the findings (e.g., even though no significant differences were found between the experimental and control groups at pre-test in any of the study variables, the groups could have differed on variables that we chose not to assess as part of this pilot design).…”
Section: Limitations and Future Researchsupporting
confidence: 76%
“…Ninety-seven students completed the intervention in one of four identical courses. A t -test comparing students who completed vs. dropped out showed that they were similar with respect to gender, age, and baseline values of the variables of interest (Dundas et al, 2017). The 97 completers (80 women, 17 men) represent the full participant sample contributing to the initial qualitative survey in the project.…”
Section: Methodsmentioning
confidence: 98%
“…The findings reported in this qualitative study were collected as part of the larger multi methods clinical study conducted on-campus at University of Bergen (Dundas et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations